Speed, steering angle and path tracking controls for a tricycle robot - Kamga, A.; Rachid, A. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
This paper is devoted to identification and control of the moving velocity of an autonomous vehicle and of the position and velocity of its steering angle. Trajectory tracking is also dealt with by adapting a simple but powerful linearization method.